2020
DOI: 10.3892/mmr.2020.11292
|View full text |Cite
|
Sign up to set email alerts
|

oxLDL promotes podocyte migration by regulating CXCL16, ADAM10 and ACTN4

Abstract: nephrotic syndrome (nS) is one of the most common causes of chronic kidney disease in the pediatric population. Hyperlipidemia is one of the main features of nS. The present study investigated the role of cXc motif chemokine ligand 16 (cXcl16) and adaM metallopeptidase domain 10 (adaM10) in oxidized low-density lipoprotein (oxldl)-stimualted podocytes and the underlying mechanisms. cXcl16 and adaM10 expression levels in oxldl-treated podocytes were measured via reverse transcription-quantitative Pcr and wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The sequences of the CXCL16 shRNA and ERK1/2 shRNA were amplified and inserted into pLKO.1-TRC control (pLKO.1) to generate recombinant plasmid for lentiviral vector production. The construction of recombinant plasmid was as previously described ( 24 ). Briefly, the sequences of shCXCL16 and shERK1/2 were amplified and inserted into pLKO.1 to generate recombinant pLKO.1-shCXCL16 and pLKO.1-ERK1/2 for lentivirus production.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the CXCL16 shRNA and ERK1/2 shRNA were amplified and inserted into pLKO.1-TRC control (pLKO.1) to generate recombinant plasmid for lentiviral vector production. The construction of recombinant plasmid was as previously described ( 24 ). Briefly, the sequences of shCXCL16 and shERK1/2 were amplified and inserted into pLKO.1 to generate recombinant pLKO.1-shCXCL16 and pLKO.1-ERK1/2 for lentivirus production.…”
Section: Methodsmentioning
confidence: 99%
“…10D) indicating a potential change in this complex's higher order structure. To our knowledge, the effect of atherosclerosis on ACTN4 has yet to be demonstrated, although exposure of oxidised LDLs (oxLDLs) to podocytes was recently shown to significantly enhance podocyte migration by increasing ACTN4 expression [109]. As a major crosslinker of actin, changes in ACTN4 are associated to alterations in cell motility and migration [110].…”
Section: Sex-conserved and -Unique Differences Identified Within Protein Structures From Human Atherosclerotic Plaquementioning
confidence: 99%
“…CXCL16 is a scavenger receptor, and its release mediates the uptake of oxLDL to induce reactive oxygen species and fibronectin in podocytes [45]. Another study revealed that ADAM10-mediated CXCL16 release modulated the actin cytoskeleton, as well as promoted podocyte migration [46]. Notably, ADAM10 has been identified as the major regulator for Notch signaling, which takes part in the development of glomerular disease.…”
Section: Podocytesmentioning
confidence: 99%